AGROECOTOURISM DEVELOPMENT AS A STRATEGY FOR RURAL AGRIBUSINESS GROWTH - Komang Shanty Muni Parwati; Komang Wirawan; Firlie Lanovia Amir (Berajah Journal, 2026)
Rural agribusiness continues to face various challenges, including limited market access, low value-added agricultural products, environmental degradation, and the need to improve community welfare. Agroecotourism has emerged as an integrated development strategy that combines sustainable agricultural practices, environmental conservation, and tourism activities to strengthen rural economic resilience. This study aims to examine the strategic role of agroecotourism development in promoting rural agribusiness growth through a comprehensive review of recent scientific literature. The research employs a qualitative literature review approach by analyzing peer-reviewed journal articles, books, and relevant institutional reports published within the last decade. The collected literature was synthesized using thematic analysis to identify the major dimensions of agroecotourism development and its implications for agribusiness sustainability. The findings indicate that agroecotourism contributes to rural agribusiness growth by diversifying farmers' income sources, increasing the value of agricultural products, expanding market opportunities, encouraging local entrepreneurship, preserving environmental resources, and strengthening community participation in rural development. Furthermore, digital promotion, stakeholder collaboration, innovation in tourism-based agricultural products, and supportive government policies are identified as critical factors influencing the successful implementation of agroecotourism. The study concludes that agroecotourism represents a sustainable development strategy capable of integrating economic, environmental, and social objectives while enhancing the competitiveness and long-term resilience of rural agribusiness. These findings provide valuable insights for policymakers, rural entrepreneurs, and researchers in designing integrated rural development policies that support sustainable agribusiness transformation.